Tindak Pidana Pengancaman dan Pemerasan dalam Penanganan Kasus Pinjaman Online - Ashifa, Kinnayah; Anjani, Maudy; Hosnah, Asmak Ul (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Advancements in technology have simplified various daily activities. However, this progress has also been exploited by illegal online loan services (pinjol) offering loans to people with low financial literacy, making it difficult to distinguish between legal and illegal services. Technologically-based loan solutions, originally intended to meet the community's urgent and long-term needs, have now been misused. This development has led to many risks and has given rise to various criminal acts, including fraud, extortion, and threats related to information and technology. The purpose of this study is normative juridical, using secondary data with qualitative data analysis methods. In Criminal Decision Number 438/Pid.Sus/2020/PN Jkt Utr, there is an explanation regarding legal protection for online loan borrowers against extortion or threats by debt collectors through electronic media. The judge decided on the second alternative accusation in the name of the defendant, Dede Supardi Bin H.Supriadi, based on Article 45, paragraph (4) Jo. Article 27, paragraph (4) of the Law of the Republic of Indonesia No. 19 of 2016 is an amendment of Law No. 11 of 2008 on Information and Electronic Transactions and Law No. 8 of 1981 on Criminal Procedure Law. Criminal charges can be imposed on the debt collectors involved in this case.